An iron-carbon composite material with strong electron transfer ability, preparation method and application thereof
By screening carbon materials with strong electron transfer capabilities and nano zero-valent iron, an iron-carbon composite material with strong electron transfer capabilities was prepared, which solved the problems of poor selectivity of existing materials and insufficient electron transfer capabilities, and achieved the effect of efficient removal of chlorinated hydrocarbon pollutants.
Patent Information
- Application Number
- CN202310048096.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-31
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-01-31
Smart Images

Figure CN116177524B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of environmental material preparation and water treatment, and in particular to an iron-carbon composite material with strong electron transfer capability, a preparation method and application thereof. Background Art
[0002] Chlorinated hydrocarbons, as an important organic solvent, are widely used in metal cleaning, dry cleaning, pesticides, printing and other fields. Due to accidental leakage during storage and improper disposal of wastewater, they have become common pollutants in soil and groundwater. Chlorinated hydrocarbons have an anesthetic effect on nerves and can cause damage to the liver, kidneys, heart, and trigeminal nerves, seriously threatening human health and environmental safety. They have been listed as one of the priority pollutants to be removed by many countries, including my country, the European Union, and the United States.
[0003] Nano-Zero-Valent Iron (Fe 0 , NZVI) has the advantages of strong reducing ability, low cost and easy preparation, and is currently one of the main methods for removing chlorinated hydrocarbons. However, there are still some problems in the process of using nano zero-valent iron to degrade chlorinated hydrocarbons. Due to the strong reducing activity of nano zero-valent iron, nano zero-valent iron is easy to react with oxygen and water, forming an iron oxide passivation layer on the surface, which hinders the contact between nano zero-valent iron and chlorinated hydrocarbons and the generation of reducing electrons. Therefore, improving the selectivity of zero-valent iron to chlorinated hydrocarbons and enhancing the electron transfer ability of nano zero-valent iron to break through the interference of the passivation layer are two important ways to effectively enhance the reduction and dechlorination ability of nano zero-valent iron. In order to solve the above-mentioned problems, a carrier with superior performance is sought to prepare a composite material of loaded stabilized NZVI, especially an iron-carbon composite material, which not only effectively solves the agglomeration phenomenon of NZVI and enhances its dispersibility, but also achieves the purpose of increasing specific surface area, reaction activity and facilitating recovery.
[0004] The commonly used preparation technology of existing iron-carbon composite materials is to select different biomass precursors to be impregnated with iron salts and then perform carbon thermal reduction or reducing agent reduction. Although the activity of nano zero-valent iron can be improved to a certain extent, the difference in the elements contained in the biomass leads to large differences in the performance of the formed iron-carbon composite materials, which is not conducive to the industrial application of the material. For example, Chinese patent CN109821883A discloses a soil chlorinated hydrocarbon remediation method based on modified zero-valent iron, which improves the selectivity of zero-valent iron for trichloroethylene through the hydrophobicity and adsorption of carbon fiber. However, the carbon fiber used in this patent has strong hydrophobicity, poor decomposition in water, weak adsorption for trichloroethylene in sewage, and reduces the removal efficiency of trichloroethylene in sewage; and the specific surface area of carbon fiber is small, and the nano zero-valent iron in the prepared material has poor dispersibility. Chinese patent CN114259984A discloses an alkali-modified biochar-loaded zero-valent iron composite material, its preparation method and application. The alkali-modified biochar further increases the specific surface area of the iron-carbon composite material, thereby enhancing the adsorption of trichloroethylene. However, the electron utilization rate of the material for the target pollutant is not evaluated, and a large amount of alkaline wastewater is generated in the process.
[0005] In view of this, the present invention provides an iron-carbon composite material with strong electron transfer ability, a preparation method and application thereof. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide an iron-carbon composite material with strong electron transfer ability, a preparation method and its application. The purpose is to prepare an iron-carbon composite material with strong electron transfer ability for selectively adsorbing chlorinated hydrocarbons, and by selecting carbon materials with high selectivity for chlorinated hydrocarbons and strong electron transfer performance, it is beneficial to promote the interference of nano zero-valent iron electrons breaking through the passivation layer, thereby improving the activity of nano zero-valent iron, and realizing the efficient and long-lasting dechlorination of chlorinated hydrocarbons by the iron-carbon composite material.
[0007] In order to solve the above technical problems, the first object of the present invention is to provide a method for preparing an iron-carbon composite material with strong electron transfer ability, comprising the following steps:
[0008] Step 1: Add the selected carbon materials to the wastewater contaminated with chlorinated hydrocarbons, and select several carbon materials with good adsorption effect on chlorinated hydrocarbons through adsorption performance test;
[0009] Step 2: Co-milling the several carbon materials with good adsorption effects on chlorinated hydrocarbons selected in step 1 with nano-zero-valent iron to prepare various iron-carbon composite materials to be characterized;
[0010] Step 3: performing electrochemical performance characterization on various iron-carbon composite materials to be characterized prepared in step 2, and screening out several carbon materials with strong electron transfer ability according to the electrochemical performance characterization results;
[0011] Step 4: The several carbon materials with strong electron transfer ability selected in step 3 are respectively used to prepare iron-carbon composite materials by liquid phase reduction method, that is, iron-carbon composite materials with strong electron transfer ability.
[0012] The beneficial effects of the present invention are: (1) The present invention prepares an iron-carbon composite material by loading nano-zero-valent iron onto a carbon material with strong electron transfer ability, thereby enhancing the selectivity of the iron-carbon composite material for chlorinated hydrocarbon organic pollutants, accelerating the enrichment of chlorinated hydrocarbons on the surface of the iron-carbon composite material, and thus increasing the reaction rate of nano-zero-valent iron to chlorinated hydrocarbons.
[0013] (2) The present invention prepares an iron-carbon composite material by loading nano-zero-valent iron with a carbon material having a strong electron transfer ability. The high conductivity of the carbon material breaks through the electron transmission resistance of the iron oxide inert layer, provides an electron transmission channel for the reduction and dechlorination of chlorinated hydrocarbons, reduces the electron transmission resistance, and thus improves the electron utilization rate of the nano-zero-valent iron.
[0014] (3) During the preparation and use of the iron-carbon composite material with strong electron transfer ability of the present invention, no additional chemical reagents need to be added to modify the material, and higher target pollutant selectivity and electron utilization efficiency can be obtained.
[0015] (4) The reaction conditions of the present invention are mild, the operation is convenient, the separation can be carried out by magnetic separation, the material cost is low, and the chlorinated hydrocarbon pollutants can be removed in a green and efficient manner, and it has certain application prospects.
[0016] Based on the above technical solution, the present invention can also be improved as follows.
[0017] Further, step 1 specifically includes the following steps:
[0018] Step 1-1: adding the selected carbon material to the wastewater contaminated with chlorinated hydrocarbons in a mass ratio of chlorinated hydrocarbons to carbon materials of (0.6-1):(2-8), and performing oscillating adsorption in a constant temperature oscillating incubator at 15-25°C for 60-72h;
[0019] Steps 1 to 2: At intervals of 0 to 48 hours, for example, 0h, 2h, 4h, 8h, 12h, 24h, 48h, and 72h, the mass content of chlorinated hydrocarbons remaining in the wastewater contaminated with chlorinated hydrocarbons is detected using a purge and trap gas chromatography-mass spectrometer, and a carbon material with a good adsorption effect having a mass content of 0 to 40% of chlorinated hydrocarbons remaining in the wastewater contaminated with chlorinated hydrocarbons is selected.
[0020] The beneficial effect of adopting the above further scheme is that the carbon material with good adsorption effect on chlorinated hydrocarbons can be selected efficiently and quickly through the above steps.
[0021] Furthermore, the carbon material with good adsorption effect includes any one of mesoporous coconut shell carbon, single-walled nanotubes with large specific surface area, nitrogen-doped mesoporous carbon balls, supercapacitor activated carbon, disordered porous carbon, ordered mesoporous carbon, and multi-walled carbon nanotubes.
[0022] Further, step 2 specifically includes the following steps: placing the carbon material with good adsorption effect on chlorinated hydrocarbons selected in step 1 and nano zero-valent iron in a ball mill according to a mass ratio of (0.5-2):1, and ball milling for 12-24 hours at room temperature under the protection of inert gas to obtain the iron-carbon composite material to be characterized. Inert gas includes nitrogen (N2), helium (He), neon (Ne), argon (Ar), etc.
[0023] Furthermore, the electrochemical performance characterization described in step 3 includes any one of an electrochemical impedance curve, a cyclic voltammetry curve, a polarization curve, and a linear voltammetry scan curve; by comparing the characterization results of the electrochemical impedance curve, cyclic voltammetry curve, polarization curve or linear voltammetry scan curve of the iron-carbon composite material to be characterized with the corresponding characterization results of the same type of nano zero-valent iron, a carbon material with a stronger electron transfer ability than nano zero-valent iron is screened out; if a carbon material with a stronger electron transfer ability than nano zero-valent iron is not screened out, steps 1 to 3 are repeated until a carbon material with a stronger electron transfer ability than nano zero-valent iron is screened out.
[0024] Furthermore, the liquid phase reduction method in step 4 is specifically as follows: first, the carbon material with strong electron transfer ability screened out in step 3 is placed in an iron salt solution and fully mixed, and then the reducing agent is added dropwise under the protection of an inert atmosphere, and stirring is continued for 0.5 to 1.0 hours after the addition, and then magnetic separation and freeze-drying are performed to obtain an iron-carbon composite material with strong electron transfer ability.
[0025] Furthermore, the mass ratio of the carbon material with strong electron transfer ability to the iron element in the iron salt is (0.5-1.5):(2-3); the iron salt is a divalent iron salt or a trivalent iron salt, the iron salt is specifically FeCl3 or FeSO4, the reducing agent is KBH4 or NaBH4, and the amount of substance ratio of the iron salt to the reducing agent is (2-3):(3-5).
[0026] Furthermore, the freeze-drying time is 12 to 24 hours, and the temperature is -50 to -80°C.
[0027] The second object of the present invention is to provide an iron-carbon composite material with strong electron transfer ability, which is prepared by any of the preparation methods described above.
[0028] The third object of the present invention is to provide an application of an iron-carbon composite material with strong electron transfer ability for the purification of contaminated wastewater containing chlorinated hydrocarbons, wherein the iron-carbon composite material with strong electron transfer ability is added to the contaminated wastewater containing chlorinated hydrocarbons in a mass ratio of (15-25): (0.06-0.1) to the chlorinated hydrocarbons.
[0029] The beneficial effect of adopting the above scheme is that the iron-carbon composite material of the present invention has good selectivity for pollutants, can be applied to sewage or groundwater with complex water components and high concentrations of coexisting components, and has good application potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a diagram of the adsorption effect of the selected carbon material of the present invention;
[0031] Figure 2 The electrochemical characterization diagram of the iron-carbon composite material to be characterized of the present invention;
[0032] Figure 3 The SEM and TEM images of the supercapacitor activated carbon loaded with nano-zero-valent iron of the present invention are shown in Figure 1, wherein (a) is a SEM image and (b) is a TEM image; Figure 4 The SEM and TEM images of the unloaded nano zero-valent iron of the present invention, wherein (a) is the SEM image and (b) is the TEM image;
[0033] Figure 5 The SEM and TEM images of the mesoporous coconut shell charcoal loaded with nano-zero-valent iron of the present invention, wherein (a) is the SEM image, and (b) is the TEM image;
[0034] Figure 6 is an X-ray diffraction (XRD) diagram of the iron-carbon composite material of the present invention;
[0035] Figure 7 The X-ray photoelectron spectrum (XPS) diagram of the iron-carbon composite material of the present invention, wherein (a) is supercapacitor activated carbon loaded with nano-zero-valent iron, and (b) is mesoporous coconut shell carbon loaded with nano-zero-valent iron;
[0036] Figure 8 This is a diagram showing the degradation effect of trichloroethylene by the iron-carbon composite material of the present invention. DETAILED DESCRIPTION
[0037] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0038] Example 1: Testing the adsorption performance of carbon materials on chlorinated hydrocarbon pollutants
[0039] In this example, trichloroethylene is selected as a characteristic pollutant, and the adsorption performance of carbon materials on chlorinated hydrocarbon pollutants is tested, wherein the carbon materials include mesoporous coconut shell carbon, supercapacitor activated carbon, single-walled nanotubes with large specific surface area, nitrogen-doped mesoporous carbon balls, multi-walled carbon nanotubes, graphene oxide, and carbon nanofibers.
[0040] The adsorption performance test of the carbon material of this embodiment on chlorinated hydrocarbon pollutants is carried out in the following specific steps:
[0041] (1) Prepare a 100 mg / L trichloroethylene solution and place it in a 100 mL crimp headspace bottle containing a polytetrafluoroethylene pad; add 50 mg of carbon material to the trichloroethylene solution and perform oscillation adsorption in a constant temperature shaking incubator at 20°C and 180 rpm for 72 h;
[0042] (2) After every 0 h, 2 h, 4 h, 8 h, 12 h, 24 h, 48 h, and 72 h, take 80 μL of the sample into a 40 mL brown sample bottle filled with ultrapure water and use a purge-and-trap gas chromatography-mass spectrometer to test the concentration of trichloroethylene in the adsorbed trichloroethylene solution at different times. The results are as follows: Figure 1 shown.
[0043] Depend on Figure 1 It can be seen that supercapacitor activated carbon, mesoporous coconut shell carbon, large specific surface area single-walled nanotubes, and nitrogen-doped mesoporous carbon spheres have better adsorption performance for trichloroethylene.
[0044] Example 2: Supercapacitor activated carbon loaded with nano-zero-valent iron iron-carbon composite material
[0045] The preparation of an iron-carbon composite material with strong electron transfer ability involved in this embodiment is carried out in the following specific steps:
[0046] (1) Supercapacitor activated carbon and nano zero-valent iron were ball-milled in a nitrogen atmosphere for 12 h at a mass ratio of 0.8:1 to obtain an iron-carbon composite material to be characterized;
[0047] (2) The iron-carbon composite material and nano-zero-valent iron to be characterized in step (1) are subjected to electrochemical testing to characterize the electron transfer ability of the carbon material. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that electrochemical characterization shows that carbon materials significantly enhance the electron transfer ability of nano-zero-valent iron, which can promote the electron transfer of nano-zero-valent iron to pollutants on the surface of iron-carbon composite materials;
[0048] (3) Under N2 atmosphere, 2.8 g supercapacitor activated carbon was added to 13.5 g FeCl3 solution, and after oscillation and mixing, 10.79 g KBH4 was added dropwise to reduce the iron salt to nano-zero-valent iron. After magnetic separation, the surface impurities were washed three times with deionized water and ethanol. After freeze-drying for 12 h, a supercapacitor activated carbon-loaded nano-zero-valent iron iron-carbon composite material was obtained. Its SEM and TEM images are shown in Figure 3 , Figure 4 These are the SEM and TEM images of nano zero-valent iron.
[0049] Example 3: Iron-carbon composite material of mesoporous coconut shell charcoal loaded with nano-zero-valent iron
[0050] The preparation of an iron-carbon composite material with strong electron transfer ability involved in this embodiment is carried out in the following specific steps:
[0051] (1) The mesoporous coconut shell carbon and nano-zero-valent iron were ball-milled in a nitrogen atmosphere for 12 h at a mass ratio of 0.8:1 to obtain an iron-carbon composite material to be characterized;
[0052] (2) performing an electrochemical test on the iron-carbon composite material to be characterized in step (1) to characterize the electron transfer ability of the carbon material;
[0053] (3) Under N2 atmosphere, 2.8 g of mesoporous coconut shell charcoal in step (3) was added to 13.5 g of FeCl3 solution, and after being shaken and mixed evenly, 10.79 g of KBH4 was added dropwise to reduce the iron salt to nano-zero-valent iron. After magnetic separation, the mixture was washed with deionized water and ethanol for 3 times to remove surface impurities. After freeze-drying for 12 h, a mesoporous coconut shell charcoal-loaded nano-zero-valent iron iron-carbon composite material was obtained. The SEM and TEM photos are shown in FIG. Figure 5 shown.
[0054] from Figure 3-Figure 5 It can be seen that the unloaded nano zero-valent iron aggregates together in large quantities, with a particle size of about 80nm, while the supercapacitor activated carbon ( Figure 3 a and Figure 3 b) and mesoporous coconut shell charcoal ( Figure 5 a and Figure 5 b) After loading the nano zero-valent iron, the nano zero-valent iron has good dispersion on the surface of the carbon material and the particle size is about 60 nm.
[0055] Figure 6 The XRD pattern of the medium iron carbon composite material (supercapacitor activated carbon loaded with nano zero-valent iron and mesoporous coconut shell carbon loaded with nano zero-valent iron) is 2θ=44°, which is Fe 0 The characteristic peak represents the (110) crystal plane. Figure 7 a and Figure 7b The XPS results of the iron-carbon composite material (supercapacitor activated carbon loaded with nano zero-valent iron and mesoporous coconut shell carbon loaded with nano zero-valent iron) show that the absorption peak at 707.3 eV is the absorption peak of zero-valent iron. The above results all indicate that nano zero-valent iron is successfully loaded onto supercapacitor activated carbon and mesoporous coconut shell carbon by liquid phase reduction method.
[0056] Example 4: Supercapacitor activated carbon loaded with nano zero-valent iron iron composite material in different proportions from Example 2
[0057] The preparation of an iron-carbon composite material with strong electron transfer ability involved in this embodiment is carried out in the following specific steps:
[0058] (1) Supercapacitor activated carbon and nano zero-valent iron were ball-milled in a nitrogen atmosphere for 12 h at a mass ratio of 0.8:1 to obtain an iron-carbon composite material to be characterized;
[0059] (2) performing an electrochemical test on the iron-carbon composite material to be characterized in step (1) to characterize the electron transfer ability of the carbon material;
[0060] (3) Under N2 atmosphere, 1.4 g supercapacitor activated carbon was added to 13.5 g FeCl3 solution and shaken to mix evenly. Then, 10.79 g KBH4 was added dropwise to reduce the iron salt to nano-zero-valent iron. After magnetic separation, the solution was washed with deionized water and ethanol three times to remove surface impurities. After freeze-drying for 12 h, an iron-carbon composite material of supercapacitor activated carbon loaded with nano-zero-valent iron was obtained.
[0061] Example 5: Supercapacitor activated carbon loaded with nano zero-valent iron iron composite material in different proportions from Example 2
[0062] The preparation of an iron-carbon composite material with strong electron transfer ability involved in this embodiment is carried out in the following specific steps:
[0063] (1) Supercapacitor activated carbon and nano zero-valent iron were ball-milled in a nitrogen atmosphere for 12 h at a mass ratio of 0.8:1 to obtain an iron-carbon composite material to be characterized;
[0064] (2) performing an electrochemical test on the iron-carbon composite material to be characterized in step (1) to characterize the electron transfer ability of the carbon material;
[0065] (3) Under N2 atmosphere, 8.4 g supercapacitor activated carbon was added to 13.5 g FeCl3 solution and shaken to mix evenly. Then, 10.79 g KBH4 was added dropwise to reduce the iron salt to nano-zero-valent iron. After magnetic separation, the solution was washed with deionized water and ethanol three times to remove surface impurities. After freeze-drying for 12 h, an iron-carbon composite material of supercapacitor activated carbon loaded with nano-zero-valent iron was obtained.
[0066] Example 6: Application of iron-carbon composite material with strong electron transfer ability
[0067] Selecting trichloroethylene as a characteristic pollutant, the iron-carbon composite material with strong electron transfer ability prepared in Example 2 and Example 3 and the iron-carbon composite material using ordinary biochar loaded with nano zero-valent iron are applied to the degradation of trichloroethylene, and the specific steps are as follows:
[0068] (1) Prepare 100 mg / L trichloroethylene solution and place it in a 100 mL crimp-top headspace bottle containing a polytetrafluoroethylene pad;
[0069] (2) 200 mg of the iron-carbon composite material prepared in Example 2 was added to the trichloroethylene solution, and the solution was shaken in a constant temperature shaking incubator at 20° C. and 180 rpm. After a certain period of time (0 d, 12 h, 1 d, 2 d, 3 d, 4 d, 5 d, 7 d), 80 μL was taken and put into a 40 mL brown sample bottle filled with ultrapure water. The concentrations of trichloroethylene and dechlorination products in the solution were tested by a purge and trap gas chromatography-mass spectrometer. The amount of hydrogen generated during the dechlorination process was detected by a gas chromatograph equipped with a TCD detector. The selectivity of the iron-carbon composite material was evaluated by quantifying the amount of electrons required for all reaction products. The degradation effect was as follows: Figure 8 shown.
[0070] The iron-carbon composite material of ordinary biochar loaded with nano zero-valent iron uses ordinary biochar prepared by pyrolysis and carbonization of biochar raw materials, and is prepared by the method of step (3) of Example 2.
[0071] Depend on Figure 8 It can be seen that compared with the degradation effect of nano zero-valent iron, the iron-carbon composite materials prepared in Example 2 and Example 3 can completely degrade trichloroethylene within 7 days, while the degradation efficiency of the iron-carbon composite material using ordinary biochar loaded with nano zero-valent iron is only about 50%.
[0072] In summary, the present invention prepares an iron-carbon composite material by loading nano-zero-valent iron on a screened carbon material with strong electron transfer ability, thereby enhancing the selectivity of the iron-carbon composite material to chlorinated hydrocarbon organic pollutants, accelerating the enrichment of chlorinated hydrocarbons on the surface of the material, and thus increasing the reaction rate of nano-zero-valent iron to chlorinated hydrocarbons.
[0073] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0074] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing an iron-carbon composite material with strong electron transfer ability, characterized in that: The steps include: Step 1: Add the selected carbon materials to the wastewater contaminated with chlorinated hydrocarbons, and select several carbon materials with good adsorption effect on chlorinated hydrocarbons through adsorption performance test; Step 2: Co-milling the several carbon materials with good adsorption effects on chlorinated hydrocarbons selected in step 1 with nano-zero-valent iron to prepare various iron-carbon composite materials to be characterized; Step 3: performing electrochemical performance characterization on various iron-carbon composite materials to be characterized prepared in step 2, and screening out several carbon materials with strong electron transfer ability according to the electrochemical performance characterization results; The electrochemical performance characterization described in step 3 includes any one of an electrochemical impedance curve, a cyclic voltammetry curve, a polarization curve, and a linear voltammetry scan curve; by comparing the characterization results of the electrochemical impedance curve, cyclic voltammetry curve, polarization curve, or linear voltammetry scan curve of the iron-carbon composite material to be characterized with the corresponding characterization results of the same type of nano zero-valent iron, a carbon material having a stronger electron transfer ability than nano zero-valent iron is screened out; If no carbon material with stronger electron transfer ability than nano zero-valent iron is screened out, repeat steps 1 to 3 until a carbon material with stronger electron transfer ability than nano zero-valent iron is screened out; Step 4: The several carbon materials with strong electron transfer ability selected in step 3 are respectively used to prepare iron-carbon composite materials by liquid phase reduction method, that is, iron-carbon composite materials with strong electron transfer ability.
2. The method for preparing an iron-carbon composite material having strong electron transfer ability according to claim 1, characterized in that: Step 1 specifically includes the following steps: Step 1-1: adding the selected carbon material to the wastewater contaminated with chlorinated hydrocarbons in a mass ratio of chlorinated hydrocarbons to carbon materials of (0.6-1):(2-8), and performing oscillating adsorption in a constant temperature oscillating incubator at 15-25°C for 60-72h; Steps 1 to 2: Every 0 to 48 hours, use a purge and trap gas chromatography-mass spectrometer to detect the mass content of chlorinated hydrocarbons remaining in the wastewater contaminated with chlorinated hydrocarbons, and select a carbon material with a good adsorption effect of 0 to 40% of the mass content of chlorinated hydrocarbons remaining in the wastewater contaminated with chlorinated hydrocarbons.
3. A method for preparing an iron-carbon composite material with strong electron transfer ability according to claim 1 or 2, characterized in that: The carbon material with good adsorption effect is mesoporous coconut shell carbon, supercapacitor activated carbon, single-walled nanotubes with large specific surface area, nitrogen-doped mesoporous carbon balls, disordered porous carbon, ordered mesoporous carbon or multi-walled carbon nanotubes.
4. The method for preparing an iron-carbon composite material with strong electron transfer ability according to claim 1, characterized in that: Step 2 specifically includes the following steps: placing the carbon material with good adsorption effect on chlorinated hydrocarbons selected in step 1 and nano zero-valent iron in a ball mill according to a mass ratio of (0.5-2):1, and ball milling them at room temperature for 12-24 hours under the protection of inert gas to obtain the iron-carbon composite material to be characterized.
5. The method for preparing an iron-carbon composite material with strong electron transfer ability according to claim 1, characterized in that: The liquid phase reduction method in step 4 is specifically as follows: first, the carbon material with strong electron transfer ability screened out in step 3 is placed in an iron salt solution and fully mixed, and then the reducing agent is added dropwise under the protection of an inert atmosphere, and stirring is continued for 0.5 to 1.0 hours after the addition, and then magnetic separation and freeze-drying are performed to obtain an iron-carbon composite material with strong electron transfer ability.
6. The method for preparing an iron-carbon composite material with strong electron transfer ability according to claim 5, characterized in that: The mass ratio of the carbon material with strong electron transfer ability to the iron element in the iron salt is (0.5-1.5):(2-3); the iron salt is a divalent iron salt or a trivalent iron salt, the reducing agent is KBH4 or NaBH4, and the molar ratio of the iron salt to the reducing agent is (2-3):(3-5).
7. The method for preparing an iron-carbon composite material with strong electron transfer ability according to claim 5, characterized in that: The freeze-drying time is 12 to 24 hours, and the temperature is -50 to -80°C.
8. An iron-carbon composite material with strong electron transfer ability, characterized in that: The method is prepared according to any one of claims 1 to 7.
9. An application of the iron-carbon composite material with strong electron transfer ability as claimed in claim 8, characterized in that: Used for purifying polluted wastewater containing chlorinated hydrocarbons, the iron-carbon composite material with strong electron transfer ability is added to the polluted wastewater containing chlorinated hydrocarbons in a mass ratio of (15-25): (0.06-0.1) to the chlorinated hydrocarbons.
Citation Information
Patent Citations
Soil chlorinated hydrocarbon remediation method based on modified zero-valent iron
CN109821883A
Alkali-modified charcoal loaded zero-valent iron composite material as well as preparation method and application thereof
CN114259984A
Preparation method and application of carbon sphere loaded nanoscale zero valent iron composite material
CN106044921A
Method for degrading hydrochloric ether in soil and resource utilization of hydrochloric ether
CN107790488A